2010
DOI: 10.1227/01.neu.0000371974.88873.15
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes and Patterns of Tumor Progression After Gamma Knife Radiosurgery for Benign Meningiomas

Abstract: GKRS demonstrates excellent long-term tumor control in the management of benign meningiomas. Tumor progression occurred at a mean time of 7.5 years after GKRS, reinforcing the need for long-term surveillance despite initial tumor control. Treatment failure was related to undercoverage of lesions in the majority of cases, with the remainder demonstrating evidence of abnormal tumor biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 22 publications
1
48
1
Order By: Relevance
“…2,20,23,31,47,50 While meningioma location within the convexity or parasagittal regions, larger tumor volume, and greater radiation dosing appear to be factors that are often predictive of an increased risk of edema, none of these variables were found to be significant in our study. 2,31,50 In the study by Patil et al, where edema was similarly defined based on new T2 signal changes on MRI, close to one-third of patients harbored meningiomas that were within the parasagittal region. Similarly, Chang et al 2 demonstrated that tumor location within the convexity region was significantly predictive of post-SRS T2 signal changes.…”
Section: Adverse Radiation Effectscontrasting
confidence: 61%
See 4 more Smart Citations
“…2,20,23,31,47,50 While meningioma location within the convexity or parasagittal regions, larger tumor volume, and greater radiation dosing appear to be factors that are often predictive of an increased risk of edema, none of these variables were found to be significant in our study. 2,31,50 In the study by Patil et al, where edema was similarly defined based on new T2 signal changes on MRI, close to one-third of patients harbored meningiomas that were within the parasagittal region. Similarly, Chang et al 2 demonstrated that tumor location within the convexity region was significantly predictive of post-SRS T2 signal changes.…”
Section: Adverse Radiation Effectscontrasting
confidence: 61%
“…Similarly, Chang et al 2 demonstrated that tumor location within the convexity region was significantly predictive of post-SRS T2 signal changes. Zada et al, 50 using a similar definition of edema, showed that lesion volume was almost double in patients who developed post-SRS edema in comparison with patients without SRS-edema (11 vs 5.7 cm 3 ). The incidence of edema in our study, however, was similar regardless of tumor location (basal or nonbasal).…”
Section: Adverse Radiation Effectsmentioning
confidence: 99%
See 3 more Smart Citations